2010
DOI: 10.1007/s11664-010-1081-z
|View full text |Cite
|
Sign up to set email alerts
|

Reflow Phenomenon Analysis of Large Scale Integrated Cu Interconnections in Via Holes by Viscoelastic Deformation Simulation

Abstract: The reflow phenomenon of Cu interconnections deposited over via holes was analyzed by viscoelastic deformation simulation using a finite-element method to clarify the embedding mechanism of Cu interconnections into via holes in a novel dual-damascene fabrication technology, which combined sputter deposition and high-pressure annealing. Cu is considered to be a viscoelastic body, and the stress distribution and deformation behavior of Cu interconnections were calculated. As a result, the deformation behavior of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The use of the sputtered Cu films may not be practical considering the maximum tolerable temperature for low-k dielectrics. The filling performance of sputtered Cu films can be improved by increasing the pressure applied during high-pressure high-temperature treatment, 24 but an upper limit to the pressure is 200 MPa because of the restrictions in the high-pressure annealing system. 13 Therefore, the following means seems to be effective in order to improve the reflow characteristics of the sputtered Cu films to realize the novel dualdamascene fabrication technology: (1) increasing the vacancy concentration in Cu films, and (2) decreasing the temperature at which defect components, i.e., vacancies or dislocations, begin to be restored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of the sputtered Cu films may not be practical considering the maximum tolerable temperature for low-k dielectrics. The filling performance of sputtered Cu films can be improved by increasing the pressure applied during high-pressure high-temperature treatment, 24 but an upper limit to the pressure is 200 MPa because of the restrictions in the high-pressure annealing system. 13 Therefore, the following means seems to be effective in order to improve the reflow characteristics of the sputtered Cu films to realize the novel dualdamascene fabrication technology: (1) increasing the vacancy concentration in Cu films, and (2) decreasing the temperature at which defect components, i.e., vacancies or dislocations, begin to be restored.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 It has been shown that Cu films deposited in vias or trenches are embedded in them through the mechanism of creep deformation during the highpressure annealing process. 24 In this case, the dominant plastic deformation mechanism is apparently core diffusion creep or Coble creep. 25 Therefore, the difference in filling performance between electroplated and sputtered Cu films may be strongly influenced by defects, such as vacancies, grain boundaries, stacking faults, etc., which control core diffusion creep and Coble creep.…”
Section: Introductionmentioning
confidence: 99%